Analysis of Biosynthetic Gene Clusters, Secretory, and Antimicrobial Peptides Reveals Environmental Suitability of Exiguobacterium profundum PHM11 - Srivastava, Alok Kumar; Srivastava, Ruchi; Bharati, Akhilendra Pratap; Singh, Alok Kumar; Sharma, Anjney; Das, Sudipta; Tiwari, Praveen Kumar; Srivastava, Anchal Kumar; Chakdar, Hillol; Kashyap, Prem Lal; Saxena, Anil Kumar (Frontiers in Microbiology, 2022)
Halotolerant bacteria produce a wide range of bioactive compounds with important applications in agriculture for abiotic stress amelioration and plant growth promotion. In the present study, seventeen biosynthetic gene clusters (BGCs) were identified in Exiguobacterium profundum PHM11 belonging to saccharides, desmotamide, pseudaminic acid, dipeptide aldehydes and terpene biosynthetic pathways representing approximately one-sixth of genome. The terpene biosynthetic pathway was conserved in Exiguobacterium spp.while E. profundum PHM11 genome confirms the presence of DXP pathway for the isopentenyl diphosphate (IPP) synthesis. Further, 2877 signal peptides (SPs) were identified using PrediSi server, out of which, 592 proteins were prophesied for the secretion having transmembrane helix (TMH). In addition, antimicrobial peptides (AMPs) were also identified using BAGEL4. The transcriptome analysis of PHM11 under salt stress reveals the differential expression of putative secretion and transporter genes having SPs and TMH. Priming of the rice seeds with PHM11 under salt stress led to improvement in the root length, root diameters, surface area, number of links and forks and shoot length etc. The study shows that the presence BGCs, SPs, and secretion proteins constituting TMH, AMPs provide superior competitiveness in the environment and make E. profundum PHM11 as a suitable candidate for plant growth promotion under salt stress.